2017
DOI: 10.1002/2017jc013165
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Variability Related to Sea Level Variability in the Pacific Ocean

Abstract: Ocean tides are changing worldwide for reasons unrelated to astronomical forcing. Changes in tidal properties coupled with altered mean sea level (MSL) may yield higher peak water levels and increased occurrence of short‐term exceedance events, such as storm surge and nuisance flooding. Here we investigate the hypothesis that changes in relative sea level are correlated with alterations in tidal amplitudes. Our approach focuses on the correlation between short‐term (monthly to interannual) fluctuations in sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 90 publications
2
75
3
Order By: Relevance
“…For K 1 , they found that most maxima occurred during late summer, and minima occurred during fall or early winter. The NWSCS neighbors Southeast Asia, and the findings of Devlin et al () are consistent with our observations at sites M1–M4 that the maximum barotropic K 1 current always occurs in summer. They speculated that the influences from the monsoon system of rains and winds or monsoon‐related oceanic responses were likely causal mechanisms.…”
Section: Discussion and Summarysupporting
confidence: 93%
See 1 more Smart Citation
“…For K 1 , they found that most maxima occurred during late summer, and minima occurred during fall or early winter. The NWSCS neighbors Southeast Asia, and the findings of Devlin et al () are consistent with our observations at sites M1–M4 that the maximum barotropic K 1 current always occurs in summer. They speculated that the influences from the monsoon system of rains and winds or monsoon‐related oceanic responses were likely causal mechanisms.…”
Section: Discussion and Summarysupporting
confidence: 93%
“…Based on seven mooring records, we find that the barotropic K 1 tidal current shows significant summer intensification over the SWG and EHI shelves. The barotropic seasonal tidal variability has been noted by many researchers in world seas, especially in coastal and polar regions, such as the Victoria Sea, North Sea, Yellow Sea and East China Sea, the north Pacific coast of North America, Southeast Asia, and the Arctic regions (Devlin et al, ; Georgas, ; Gräwe et al, ; Kang et al, ; Müller, ; Müller et al, ). Multiple factors that possess seasonal varying natures can likely bring the seasonal signal into ocean tides, for example, oceanic physical processes (e.g., stratification, bed friction, sea level, and circulation), meteorological forcings (e.g., surface wind, atmospheric pressure, rainfall, and storm surges), seasonally varying river flow and ice coverage.…”
Section: Discussion and Summarymentioning
confidence: 94%
“…However, the tides have changed differently in different regions, thereby preventing overall conclusions on common forcing factors. Regressions of tidal estimates against the low‐frequency components of MSL from sea level records suggest some degree of association between perturbations in water depth and the tide; see, for example, the analysis of UK MTR data (Woodworth et al, ) and more recent larger‐scale studies (Devlin, Jay, Talke, et al, ; Devlin, Jay, Zaron, et al, ; Devlin et al, ; Schindelegger et al, ). Moreover, recent papers have attempted to include changes in phase as well as amplitude, to provide a more complete picture of the response of tides to potential forcing factors.…”
Section: Past Changes In Tidesmentioning
confidence: 99%
“…The tide changes manifest themselves as variations in tidal constituents from year to year and can result in a long‐term trend in tidal parameters if a corresponding trend exists in the nontidal forcing. Without discriminating between the sources of the sea level fluctuations, Devlin, Jay, Talke, et al (), Devlin, Jay, Zaron, et al () investigated tide gauge records in the Pacific Ocean, and their results suggest that interannual tidal variability is correlated to sea level variability at most (92%) of tide gauges in the Pacific, with statistically significant rates between ±1% and ±50% of the MSL rise observed. However, the correlations of the multiple mechanisms inducing tide and sea level variability make it challenging to discern the individual causes of observed variability.…”
Section: Potential Mechanisms Causing Changesmentioning
confidence: 99%
“…Changes in the internal tide may also be a factor; part of the rise in MSL is due to increased surface water temperature and stratification, and previous studies have explored the link between sea level rise and tidal evolution related to changes in stratification (Colosi & Munk, ; Müller, ; Müller et al, ) and MSL rise (Arbic et al, ). For a more detailed discussion of the mechanisms that may influence tides and MSL, the reader is directed to recent works (Devlin, Jay, Talke, et al ; Devlin, Jay, Zaron, et al, ).…”
Section: Introductionmentioning
confidence: 99%